Teodoro Hampe Martínez: Important historian and scholar in Peru - Adriazola, Juan Carlos (Mercurio Peruano, 2016)
Teodoro Werner Hampe Martínez was born in Miraflores, Lima, in 1960, and after studying at the Peruvian-German school, he began a brilliant career at the Pontifical Catholic University of Peru. His fruitful intellectual life in the field of history is worthy of admiration, not only for the quality of his writings, but also for the number of articles, essays, reviews, compilations and books that he has left published in the Spanish language, but also in German, French and English in various journals.